(untitled) (Third Sector Social Economic Review, 2019)
In this study, the concept of job boredom in the national literature, which has not been studied sufficiently, has been studied and the effect of the job crafting on job boredom has been determined. In the study, the data were obtained from the employees of manufacturing sector and the necessary statistical analyzes were made according to the research purpose. The findings showed that both the job crafting and job boredom scales were the reliability and validity. Thus, it is determined that the job crafting scale and job boredom scale can be used in the Turkish context. In addition, the analysis findings showed that the dimensions of “increasing structural job resources” and “increasing social job resources” of the job crafting have a negative effect on job boredom; the dimension of “increasing challenging job demands” of the job crafting have a positive effect on job boredom. It was determined that job crafting in general negatively affected the job boredom, namely, the job boredom decreased due to the increase of job crafting.